Development of a customized three-dimensional airway model (Research, Society and Development, 2022)
This study aimed to develop a customized, three-dimensional airway model based on relevant medical images, using additive manufacturing techniques. We evaluated the model’s ability to replicate the dimensions of the images acquired from the chest of a patient using multi-detector computed tomography (CT). Using dedicated software, a three-dimensional mesh was created based on the images. A multi-detector CT study of the full-scale printed three-dimensional airways model was subsequently carried out to compare its dimensions with that of the original study at four predetermined points. The observed median differences at the four points were 0.4 mm (p = 0.686), -1.3 mm (p = 0.138), 0.7 mm (p = 0.141), and 0.1 mm (p = 0.892). The intraclass correlation coefficient between the measurements made on the patient and those on the model was 0.98 (95% confidence interval: 0.96–0.99, p < 0.001). We successfully developed a three-dimensional model of the airway based on its corresponding medical images. The differences in the dimensions between the model and the original images were in line with those observed in previous studies and are presumably irrelevant for most applications.